Bolívar par l’image ou les travestissements de l’histoire - Frédérique Langue (Caravelle)
The political uses of the past find in the “cult of Bolívar” and in “Bolivarianisms” an enlightening illustration of the recourse to the nation's founding figures, reinterpreted by Venezuelan rulers over time. The images of the nation's founder in the broad sense, that is the medias that portray him (all kinds of representations such as feature films or documentaries for the cinema), are part of a national imaginary reinterpreted by Hugo Chávez. The image of the hero appears to be an ideological reconstruction in the long term, from the Revolution of Independence to the present day, where Chávez appears to be the “Bolivar of the 20th/ 21st century”. So, this essay will attempt to decipher the instrumentalization of history through both an official and a visual mode, especially via the cinema, along with the backlash this has caused in a country deeply divided and scarred by the dictatorship.